2003
DOI: 10.1093/bja/aeg243
|View full text |Cite
|
Sign up to set email alerts
|

Patient well-being after general anaesthesia: a prospective, randomized, controlled multi-centre trial comparing intravenous and inhalation anaesthesia

Abstract: Total i.v. anaesthesia improves early postoperative patient well-being and reduces the incidence of PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 22 publications
(11 reference statements)
3
68
1
3
Order By: Relevance
“…A total of 13 trials reported pain intensity at or around 2 h postsurgery, in which 686 patients received anaesthesia using propofol for maintenance, while 668 were given inhalational anaesthesia [10,11,[18][19][20][21][22][23][24][25][26][27][28]. Overall, pain scores were not significantly different between experimental groups (Hedge's g (95%CI) À0.120 (À0.415-0.175) (p = 0.425) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 13 trials reported pain intensity at or around 2 h postsurgery, in which 686 patients received anaesthesia using propofol for maintenance, while 668 were given inhalational anaesthesia [10,11,[18][19][20][21][22][23][24][25][26][27][28]. Overall, pain scores were not significantly different between experimental groups (Hedge's g (95%CI) À0.120 (À0.415-0.175) (p = 0.425) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of nine trials reported pain intensity at or around 24 h postsurgery, in which 595 patients received propofol anaesthesia, while 586 had inhalational anaesthesia [10,11,18,19,21,22,25,28,29]. Overall, compared with inhalational anaesthetics, patients who received propofol reported significantly lower pain scores 24 h postsurgery (Hedge's g (95% CI) À0.134 (À0.248 to À0.021) (p = 0.021) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[70][71][72][73][74] Among eight studies using volatiles, four found acupuncture effective for PONV, 52,54,60 and one found acupuncture effective for vomiting, 6 but not for nausea. One study using intravenous anesthesia found acupuncture effective, 59 and one found it was not effective.…”
Section: Anesthesia As Risk Factor For Ponvmentioning
confidence: 99%